HUBUNGAN RESPONSE TIME PERAWAT DENGAN KEPUASAN KELUARGA PASIEN DI INSTALASI GAWAT DARURAT RSUD Dr. PIRNGADI KOTA MEDAN - Normi Sipayung; Janno Sinaga; Henny Syapitri (Jurnal Reproductive Health, 2018)
Response time is fully committed to the patient time when patients arrive until response or a response from the emergency room. The speed of the service in this context is the implementation of the act or examination by physicians and nurses in less than five minutes from the first arrival in er patient. Patient satisfaction family is based on the fulfillment hope the patient and family. The gratification of the family closely related to response time (time responding). The purpose of aware of the relationships response time a nurse with satisfaction the family patients in emergency room RSUD Dr.Pirngadi city medan. This is the kind of research descriptive correlation with delightful the study of cross sectional. The population of this research was 320 people by the number of sample of the 48 patients taken with relatives of the accidental of sampling techniques. Collecting data was done using a questionnaire and observation, then the data analysis by test chi-square. Based on the research indicates the presence of the relation of response time a nurse with the family satisfaction atients in emergency room RSUD Dr.Pirngadi city medan (p=0.002; a 0.05). Based on the result of the study can be in conclude that Rapid response time to increase life expectancy for patients, prevent a disability physical or death, and to increase the satisfaction of the family and the patient against services offered by hospital. Hence advised for hospitals, relations with leaves response time a nurse with satisfaction hospital patient and the management team can implement intervention to increase the satisfaction of the family patient against response time nurse.